Pleura Fluid Leukocyte Levels Test in Establish of Pleura Tuberculosis Effusion in Exudative Pleural Effusion Patients at H. Adam Malik General Hospital Medan in 2018 - Selvy Wulandari; Fajrinur Syahrani; Ade Rahmaini; Putri Chairani Eyanoer (Jurnal Respirologi Indonesia, 2021)
Background: Tuberculous pleural effusion is an accumulation of fluid in the pleural cavity produced by Mycobacterium tuberculosis (MTB). The gold standard of TB pleural effusion diagnosis is to obtain TB bacilli in pleural fluid or pleural tissue. However, this is often constrained due to the low identification level of these bacilli and the slow growth of MTB cultures. This study aimed to assess the pleural fluid leukocyte level in establishing a diagnosis of pleural effusion caused by TB. Methods: This was a diagnostic study conducted on 111 patients with pleural effusion, caused by TB, malignancy or non-TB infections that were assigned by supporting examinations obtained from medical records, which then assessed for pleural fluid leukocytes. Statistical analysis was performed using Kruskal Wallis Test and Receiver Operating Characteristic (ROC) curve to attain the cut-off point of pleural fluid leukocyte level. Results: Pleural fluid leukocyte levels in TB cases were significantly different when compared to pleural effusion caused by malignancy and non-TB infections (P<0.001). Pleural fluid leukocyte level ≥1100 cell/mm3 was a cut-off diagnostic test for tuberculous pleural effusion with a sensitivity of 77% and specificity of 60.3%. Conclusion: Pleural fluid leukocyte level ≥1100 cell/mm3 could assist in diagnosing tuberculous pleural effusion.